Crushing the Bones of the Other: Disability, Ethnicity, and Homosexuality in Rashid Al-Daif's Sikirida's Cat and Alexandra Chreiteh's Ali and His Russian Mother. Issue 3 (27th May 2017) - Sinno, Nadine
ABSTRACT: This article offers a textual analysis of Rashid Al-Daif's Sikirida's Cat and Alexandra Chreiteh's Ali and His Russian Mother, focusing on the novels' exploration of disability, gender, sexuality, and ethnicity. I contend that both novels reveal the violence of exclusionary cultural discourses and practices that render the nation's "Others" in a constant state of vulnerability by virtue of their stigmatized gender, sexuality, ethnicity, and/or corporeal difference. The novels give voice to emergent subjectivities that—while still marginalized—are no longer subdued by dominant discourses of disavowal and exclusion. Furthermore, no longer are the struggles of non-normative characters foreshadowed by the text's preoccupation with war and security (or the lack thereof). By vividly portraying the lived realities of minoritized characters who struggle against hegemonic notions of gender, sexuality, ability, and citizenship, al-Daif and Chreiteh's texts reveal and interrogate multiple discourses of oppression, including sexism, homophobia, ableism, and xenophobia.